Altered Cellular Kinetics in Growth Plate according to Alterations in Weight Bearing - Park, Hoon (Yonsei University College of Medicine, 2012)
PURPOSE: To examine the effects of change in weight bearing on the growth plate metabolism, a simulated animal model of weightlessness was introduced and the chondrocytes' cellular kinetics was evaluated. MATERIALS AND METHODS: Unloading condition on the hind-limb of Sprague-Dawley rats was created by fixing a tail and lifting the hind-limb. Six rats aged 6 weeks old were assigned to each group of unloading, reloading, and control groups of unloading or reloading. Unloading was maintained for three weeks, and then reloading was applied for another one week thereafter. Histomorphometry for the assessment of vertical length of the growth plate, 5-bromo-2'-deoxyuridin immunohistochemistry for cellular kinetics, and biotin nick end labeling transferase-mediated deoxyuridine triphosphate-biotin nick end labeling (TUNEL) assay for chondrocytes apoptosis in the growth plate were performed. RESULTS: The vertical length of the growth plate and the proliferative potential of chondrocytes were decreased in the unloading group compared to those of control groups. Inter-group differences were more significant in the proliferative and hypertrophic zones. Reloading increased the length of growth plate and proliferative potential of chondrocytes. However, apoptotic changes in the growth plate were not affected by the alterations of weight bearing. CONCLUSION: Alterations in the weight bearing induced changes in the chondrocytic proliferative potential of the growth plate, however, had no effects on the apoptosis. This may explain why non-weight bearing in various clinical situations hampers normal longitudinal bone growth. Further studies on the factors for reversibility of chondrocytic proliferation upon variable mechanical stresses are needed.